PEMANFAATAN DATA HUJAN BERBASIS SATELIT CHIRPS UNTUK PEMETAAN HUJAN RANCANGAN DI KABUPATEN LOMBOK UTARA - SAIDAH, HUMAIRO; WIRADHARMA, LALU WIRAHMAN; SUPRIYADI, ANID; KAMTIKA, MIA JULIA (Universitas Mahasaraswati K. Mataram, 2024)
The design rainfall value is a critical parameter in flood analysis and water structure design. In general, the design rainfall calculation uses measured rainfall data. However, sometimes it is difficult to find complete rainfall data from evenly distributed rainfall stations and in an extended measurement range. This study aims to test the use of CHIRPS satellite-based rainfall data as an alternative solution for providing data in areas with difficulty with rainfall data. The analysis includes data accuracy and calibration evaluation, followed by design rainfall analysis with frequency analysis and mapping using spatial data processing software. The accuracy test results obtained an average deviation value of the original CHIRPS that did not meet the average NSE value of 0.346. Furthermore, the data was calibrated using the regression method, and corrected data was obtained with an NSE of 0.446 with an interpretation of the meeting. A rainfall analysis was conducted for corrected CHIRPS with ARR (Automatic Rainfall Recorder) measurement as a control. The results obtained the average percentage deviation for design rainfall with a return period of 2, 5, 10, 25, 50, and 100 years using corrected CHIRPS ranging from 18 - 28% lower than design rainfall using ARR. The design rainfall isohyet map using spatial data processing software for the North Lombok Region shows that high design rainfall occurs in the eastern part of North Lombok, namely around the Santong and Sambik Bangkol stations, while design rainfall with low values is in the western part of North Lombok, namely around the Tanjung and Gunungsari stations.